Estudo comparativo entre os aços galvanizado S235 e inox 304 aplicados na construção de torre de resfriamento submetida a ação dinâmica e comportamento não linear - Filho, Paulo Almir Borges de Sousa (2023)
The present investigation is focused on the evaluation of two types of steel, stainless 304 and galvanized S235, applied in steel structures builds commonly present in cooling towers. This equipment is widely found in industries, such as sugar and alcohol, and can be exposed to corrosion according to the properties of the fluids inherent to the process. This coupled with vibrations can make them more susceptible to failure. It is necessary to analyze the structural integrity, checking critical points and the displacements, loads and tensions of the entire structure. The analysis is based on the direct stiffness method, using bar and truss elements in a three-dimensional reference system, with static and dynamic modules. For the time-dependent analysis, Newmark's algorithm is applied considering the system unconditionally stable with respect to the adopted time increment. A bilinear constitutive model with linear hardening is used to describe the elastic-plastic behavior of the materials, while corrosion is considered as a homogeneous reduction in the cross-sectional area of the bars. To solve the non-linear finite element problem, routines were written in Fortran and examples from the literature were analyzed in order to check the accuracy of the results. In the case study, the input loads were based on data collected through software in field analysis. Static and dynamic analyzes are performed for both materials, with and without corrosion, establishing a comparison between the effects of nonlinearities and the structure response according to the materials used. The results prove the better behavior of stainless steel 304 compared to galvanized structural steel S235 W, when 50% corrosion is induced in part of the structure, especially when analyzing the response in the plastic phase of the elements. Critical elements are identified in order to propose a corrective intervention to prevent the collapse of the structure.